Fe/Cu diatomic catalysts for electrochemical nitrate reduction to ammonia - Shuo Zhang; Jianghua Wu; Mengting Zheng; Xin Jin; Zihan Shen; Zhonghua Li; Yanjun Wang; Quan Wang; Xuebin Wang; Hui Wei; Jiangwei Zhang; Peng Wang; et al. (Nature Communications, 2023)
Abstract Electrochemical conversion of nitrate to ammonia offers an efficient approach to reducing nitrate pollutants and a potential technology for low-temperature and low-pressure ammonia synthesis. However, the process is limited by multiple competing reactions and NO3 − adsorption on cathode surfaces. Here, we report a Fe/Cu diatomic catalyst on holey nitrogen-doped graphene which exhibits high catalytic activities and selectivity for ammonia production. The catalyst enables a maximum ammonia Faradaic efficiency of 92.51% (−0.3 V(RHE)) and a high NH3 yield rate of 1.08 mmol h−1 mg−1 (at − 0.5 V(RHE)). Computational and theoretical analysis reveals that a relatively strong interaction between NO3 − and Fe/Cu promotes the adsorption and discharge of NO3 − anions. Nitrogen-oxygen bonds are also shown to be weakened due to the existence of hetero-atomic dual sites which lowers the overall reaction barriers. The dual-site and hetero-atom strategy in this work provides a flexible design for further catalyst development and expands the electrocatalytic techniques for nitrate reduction and ammonia synthesis.